2009
DOI: 10.1021/mp800199w
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Shell-Cross-Linked Knedel-like (cSCK) Nanoparticles for Highly Efficient PNA Delivery

Abstract: Peptide nucleic acids have a number of features that make them an ideal platform for the development of in vitro biological probes and tools. Unfortunately, their inability to pass through membranes has limited their in vivo application as diagnostic and therapeutic agents. Herein, we describe the development of cationic shell-crosslinked knedel-like (cSCK) nanoparticles as highly efficient vehicles for the delivery of PNAs into cells, either through electrostatic complexation with a PNA•ODN hybrid, or through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 37 publications
1
69
0
Order By: Relevance
“…[4,5] For example, shell-cross-linked nanoparticles (SCKs) have been pioneered by Wooley's and other groups since the late 1990s for various applications, e.g., drug and gene delivery. [6,7] However, in another consideration, it is expected that drugs encapsulated in micelles can be specifically and more rapidly released in the interior of targeted cells to enhance their functions. [8][9][10] Maintenance of cross-linkages of the micellar shell may indeed act as a barrier to intracellular drug release.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] For example, shell-cross-linked nanoparticles (SCKs) have been pioneered by Wooley's and other groups since the late 1990s for various applications, e.g., drug and gene delivery. [6,7] However, in another consideration, it is expected that drugs encapsulated in micelles can be specifically and more rapidly released in the interior of targeted cells to enhance their functions. [8][9][10] Maintenance of cross-linkages of the micellar shell may indeed act as a barrier to intracellular drug release.…”
Section: Introductionmentioning
confidence: 99%
“…N-Hydroxybenzotriazole H 2 O (HOBT) and 2-(1H-benzotriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HBTU) were purchased from EMD Chemicals, Inc. The amphiphilic block copolymer, poly(acrylic acid) 60 -block-polystyrene 30 (PAA 60 -b-PS 30 ), was prepared according to literature [33], and transformed into poly(acrylamidoethylamine) 160 -block-polystyrene 30 (PAEA 160 -b-PS 30 ) for the preparation of the cSCKs [44]. CellTiter 96 non-radioactive cell proliferation assay was purchased from Promega.…”
Section: Methodsmentioning
confidence: 99%
“…ODN hybrids and DNA by an endocytotic mechanism [33]. By adjusting the N/P ratio, the cSCK binding affinity could be optimized for the binding and delivery of the PNA-YR 9 .…”
Section: Rsfsroyalsocietypublishingorg Interface Focus 3: 20120059mentioning
confidence: 99%
“…Having the antisense agent covalently bound to the NP runs the risk, however, that much of it may remain trapped in endosomes along with the NP. This appeared to be the case in a study with shell cross-linked NP linked to antisense PNAs via an amide linkage that did not show bioactivity, whereas the same PNAs linked via a bioreductively cleavable disulfide linker did [130]. confocal studies showed that while the PNA was able to exit the endocytic compartments and enter the cytoplasm, the NP was not.…”
Section: Antisense Imaging Agent Deliverymentioning
confidence: 97%